HBx Mediated Increase of DDX17 Contributes to HBV-Related Hepatocellular Carcinoma Tumorigenesis - Dong, Mei-Ling; Wen, Xu; He, Xin; Ren, Ji-Hua; Yu, Hai-Bo; Qin, Yi-Ping; Yang, Zhen; Yang, Min-Li; Zhou, Chong-Yang; Zhang, Hui; Cheng, Sheng-Tao; Chen, Juan (Frontiers in Immunology, 2022)
HBV is strongly associated with HCC development and DEAD-box RNA helicase 17 (DDX17) is a significant member of the DEAD box family which plays a key role in HCC development by promoting cancer metastasis. However, the important role of DDX17 in the pathogenesis of HBV-related HCC remains unclear. In this study, we aim to investigate the functional role of DDX17 on HBV and HBV-induced HCC development. Based on data from GEO database and HBV-infected cells, we found that DDX17 was upregulated by viral protein HBx. Mechanically, increased DDX17 could promote HBV replication and transcription via upregulating ZWINT. Further study showed that DDX17 could promote HBx-mediated HCC metastasis. Finally, the promotion of DDX17 on HBV and HBV-related HCC were confirmed in vivo. In general, we revealed a novel role of DDX17 on HBV and HBV-related HCC metastasis.